2017
DOI: 10.1155/2017/5635929
|View full text |Cite|
|
Sign up to set email alerts
|

Anti-Interleukin-22-Neutralizing Antibody Attenuates Angiotensin II-Induced Cardiac Hypertrophy in Mice

Abstract: Background Interleukin- (IL-) 22 is considered a proinflammatory cytokine. Recent evidence has demonstrated that it plays a role in cardiovascular diseases. In the recent study, we investigate whether IL-22 is involved in cardiac hypertrophy. Methods Angiotensin II was used to build hypertrophy model and the IL-22 and IL-22 receptor 1 (IL-22R1) levels in heart tissue were measured. In addition, angiotensin II-treated mice received an injection of anti-IL-22-neutralizing antibody (nAb) to investigate the effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 34 publications
1
21
0
Order By: Relevance
“…IL-22 is an immune-related cytokine secreted primarily by macrophages and CD4 + T lymphocytes. An increasing number of studies have reported that IL-22 expression is increased in inflammation-mediated cardiovascular disease (16)(17)(18)(19)(20)(21). Previous studies reported that both T helper (Th) 22 and IL-22 levels were increased in Coxsackie virus B3-induced acute and chronic viral myocarditis and dilated cardiomyopathy (26,27).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…IL-22 is an immune-related cytokine secreted primarily by macrophages and CD4 + T lymphocytes. An increasing number of studies have reported that IL-22 expression is increased in inflammation-mediated cardiovascular disease (16)(17)(18)(19)(20)(21). Previous studies reported that both T helper (Th) 22 and IL-22 levels were increased in Coxsackie virus B3-induced acute and chronic viral myocarditis and dilated cardiomyopathy (26,27).…”
Section: Discussionmentioning
confidence: 99%
“…no. AF-100-21M-2; PeproTech, Inc.) (17,26,27), and saline treatment as control. Following treatment at 37˚C for 12 h, fibrosis expression in cardiac fibroblasts was detected.…”
Section: Measurement Of Plasma Il-22 and Tgf-β1 Levelsmentioning
confidence: 99%
See 1 more Smart Citation
“…IL-17 seems to have dose-and cell source-dependent inflammatory and pro-fibrotic effect, whereas interleukin 22 (IL-22) was associated with protecting against liver fibrosis through downregulation of the TGF-b1/Notch signaling pathway [194] but being pro-fibrotic in cardiac fibrosis through STAT3/and ERK and IL-17, IL-6, IL-1b, IFN-g, and TNF-a [195] and pro-atherosclerotic [196]. Both, IL-17 and IL-22 are associated with poor prognosis in liver cancer [197], but the exact roles of IL-17 and IL-22 need to be defined in detail in regard to concentration, kind of inflammation, and period of chronic inflammation involved in signaling axis and cell sources.…”
Section: Disruption Of Gut Bacteria Composition As Internal Pathogenimentioning
confidence: 99%
“…In the article “Anti-Interleukin-22-Neutralizing Antibody Attenuates Angiotensin II-Induced Cardiac Hypertrophy in Mice” [ 1 ], there was an error in Figure 1(a) , where the IL-22, β -MHC, and GAPDH bands were triplicated, due to a production error. The corrected figure is shown below.…”
mentioning
confidence: 99%